El Aula del Futuro para integrar el modelo STEAM en las instituciones educativas de Educación Básica - Flores Caiza, Dennys Paúl (2023)
The advancement of science and technology allow a great capacity of access to information. Ecuadorian education must respond to new social challenges, training trained professionals for this new era, unfortunately the gap that exists between education and society has led to educational centers not fulfilling a training role in accordance with labor demand. Due to the expired individualistic and memory training processes, aggravated by an educational space or classroom that prevents cognitive, creative and social development. The objective of this work was to design a proposal for the classroom of the future to integrate the STEAM model in educational institutions of Basic Education. A quantitative investigation with a descriptive approach was carried out through the application of a measurement instrument that consists of a questionnaire on the characteristic variables, technical and pedagogical requirements that the classroom of the future must have from the teacher's perception in our Ecuadorian context, where studied two private institutions and two fiscal institutions of Basic Education in the urban sector of the Riobamba-Chambo district. As a sample, 4 educational institutions were taken, choosing 5 teachers from each of the educational institutions, from a total population of 155 teachers. After obtaining the data, they were analyzed and it was determined from the perception of the teachers which are the characteristics both in innovation, architecture and pedagogy, designing the classroom of the future as a training space that includes ICTs and connectivity as a learning tool, for through active pedagogy.